Challenges in using ICT Gadgets to cope with effects of COVID-19 on Education: A short survey of online teaching Literature in English - Gabriel, Bazimaziki (International Journal of Humanities and Education Development (IJHED), 2020)
Covid-19 pandemic has slowed down progress in many sectors of human life worldwide and education has considerably been affected from pre-primary to tertiary levels. Coping with this pandemic resulted in the move to E-leaning from face - to- face teaching whereby a number of challenges are impeding the intended learning outcomes. In this study, Introduction to Literature in English is focused with specific interest in undergraduate students. While they should be taught Literature to be equipped not only with ethical values, critical thinking and analytical skills but also communication skills in English; online teaching challenges them hence jeopardizing the intended goal due to a number of factors such as limited or lack of ICT skills and resources which make online learning during the COVID-19 lockdowns not inclusive.